Analisis Model-Model Program Pemberdayaan Masyarakat Melalui Simpan Pinjam Kelompok Masyarakat di Provinsi Riau - yati, ardi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
The objective of the research is to identify the programs of community empowerment activities in the form of savings and loan groups in Riau Province and then compare the results. Object of research activities of community empowerment through group savings and loan. The research method used is descriptive qualitative with observation, interview and update research data of similar program in Riau Province. The result of the research is the discovery of various types of community empowerment activities in the form of group savings and loan activities. The activities are women's savings and loans group which is part of PNPM Mandiri Pedesaan Program, Productive Economic Business Activities (UED-SP) which is part of Village Empowerment Program (PPD) and Village Economic Institute (LED) program. Various activities are very useful in the growth of microeconomics. The savings and loan activities located in the village are preferred because they are closer and felt the benefits. This condition makes the PNPM Mandiri Rural Savings and Loans Activities located in the subdistrict less desirable. It is necessary for the management of savings and loan fund management institutions to be sustainable even though the program mentoring period has been completed. There needs to be cooperation between the group savings and loan management institutions so that the funds can be of maximum benefit to the community.